Análisis documental del apoyo familiar y pautas psicoactivas en la prevención del abuso sexual infantil. (2021)
The general objective of the following research project is to analyze family training in psycho-affective guidelines for the prevention of child sexual abuse, in order to fulfill this objective, the authors carried out a documentary review based on the categories of analysis and later, they were analyzed in an artisan matrix made in Excel. The literature review revealed that today, the level of training that families have in psycho-affective practices is low, and this is precisely one of the factors associated with the insecurity of children to express and identify any situation risk of ASI.